On the Relationship Between Foreign Direct Investments and Economic Growth. Romania in Times of Crisis - Oana-Ramona Socoliuc; Andreea-Oana Iacobuta; Delia-Elena Diaconasu (CES Working Papers, 2014)
Foreign direct investments might be perceived as the engine of growth and economic development for both developed and developing economies. For of Romania, a country with a closed regime in the past, their role is even more important in promoting prosperity and social wealth. In the context of EU integration, Romania had benefited from a large amount of foreign direct investments coming especially from the major European economies, but such ascending trend with positive implications towards economic and social areas was all at once interrupted by the recent financial crisis. The deep recession in Romania along with numerous internal disequilibria had a negative impact on those who want to invest in this perimeter. In such circumstances the purpose of this paper is to investigate the effects of the crisis on FDI flows and consequently, on Romania's development potential using a Granger causality analysis. The results highlight that FDI inflows have a prominent benefic influence on economic growth and that Romanian economic climate is not ready to ensure the bidirectional nexus.
Keywords: F21; G01; 330; foreign direct investment; economic growth; crisis